2020
DOI: 10.3389/fonc.2020.01353
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Assessment of Cervical Cancer Patients by Clinical Staging and Surgical-Pathological Factor: A Support Vector Machine-Based Approach

Abstract: Introduction: The International Federation of Gynecology and Obstetrics (FIGO) staging system is considered the most powerful prognostic factor in patients with cervical cancer. In addition, other surgical-pathological risk factors have been demonstrated to have significance in predicting the prognosis of patients. Therefore, the purpose of this study was to investigate the effects of the FIGO staging system and surgical-pathological risk factors on the prognosis of cervical cancer patients. Methods: A retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The cumulative survival rates for early and late stages of disease in this study (78.9% and 56.7% respectively) are comparable with a study conducted in India (84% and 8.1% respectively) [13]. The variations may be due to the duration of follow-up time.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…The cumulative survival rates for early and late stages of disease in this study (78.9% and 56.7% respectively) are comparable with a study conducted in India (84% and 8.1% respectively) [13]. The variations may be due to the duration of follow-up time.…”
Section: Plos Onesupporting
confidence: 83%
“…Socioeconomic, demographic, and medical variables like age, marital status, origin, occupation, histological type are known to be associated with survival [11] Many cultural factors contribute to the acquisition of HPV and its progression to cancer which include high parity, early marriage, multiple sexual partners, and diseases that reduce immunity status [12]. These were also among the possible predictors associated with higher cervical cancer mortality among women in addition to early age at first sexual intercourse, advanced cervical cancer disease condition, smoking, and use of oral contraceptives [13] [14]. It was observed that retired and divorced women had lower survival rates than other women [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancers (CC) are the 3 rd most common cancer in women worldwide [ 1 ], and human papillomavirus (HPV)16 and 18 account for more than 70% of CC [ 2 ]. Clinically, the International Federation of Gynecology and Obstetrics (FIGO) cervical cancer staging system is the most powerful prognostic factor in patients with cervical cancer and useful guidance for treatment [ 3 , 4 ]. Stage-I CC cells have grown from the surface of the cervix into deeper tissues, while stage-II cancer is 4 cm or larger, and grows beyond the cervix and uterus, but hasn’t spread to the walls of the pelvis or the lower part of the vagina.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the International Federation of Gynecology and Obstetrics (FIGO) Cervical cancer staging system is an effective prognostic factor in patients with cervical cancer and useful guidance for treatment [ 10 ]. Stage I CC cells have grown from the surface of the cervix into deeper tissues.…”
Section: Introductionmentioning
confidence: 99%